2003
DOI: 10.1086/502264
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Sterilization Practices: Evidence for Event-Related Outdating

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Cambridge University Press and ABSTRACTWe administered a web-based questionnaire to SHEA, APIC, and EIN members to assess the frequency of fires associated with alcohol-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 5 publications
(2 reference statements)
0
24
0
5
Order By: Relevance
“…Such a burden is not without associated costs in materials and manpower as already shown. 18 At present the guidance on storage times following sterilisation in primary care does not appear to be evidence-based and the recommendations are not supported by this study.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Such a burden is not without associated costs in materials and manpower as already shown. 18 At present the guidance on storage times following sterilisation in primary care does not appear to be evidence-based and the recommendations are not supported by this study.…”
Section: Discussionmentioning
confidence: 68%
“…At a conservative estimate of just AUS $5 per item to cover the manpower and equipments costs, the annual bill to reprocess these unused instruments was estimated to be in the order of AUS $90,000. 18 At present there appears to be a lack of evidence in the dental literature on the length of time sterile instruments may remain bagged before use, which brings into question the validity of the current UK guidance to primary care dentists. If a sterilised item can be considered to be sterile almost indefinitely then provided the packaging remains dry and intact, HTM 01-05, 5 with its 60 day recommendation, appears to be placing an extra and possibly unnecessary burden on UK primary care dentists.…”
Section: Discussionmentioning
confidence: 99%
“…An experiment (17) was conducted to compare the shelf life of sterilized materials with the "event-related" control. This paradigm assumes that the sterilized and suitably packaged material remains in this condition until the package is damaged, which may occur due to humidity, tears, dents or breakage of the seal (18) .…”
Section: Summary Of Experiments That Included the Evaluation Of The Cmentioning
confidence: 99%
“…Other studies indicated temperature and/or humidity were not controlled or monitored during storage periods and results of sterility testing did not indicate higher levels of contamination. 17,18 Webster et al 19 attempted to examine the effect of a variety of controlled and uncontrolled storage conditions in their study over a 2-year period. One interesting finding was from testing articles Specifications for temperature and humidity in sterile storage environments Healthcare Infection Specifications for temperature and humidity in sterile storage environments Healthcare Infection stored in a box in the rear of a car for 9 years.…”
Section: Healthcare Infection T Mcauleymentioning
confidence: 99%